2012
DOI: 10.1007/s00726-012-1332-9
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of leucine catabolism in mammary epithelial cells

Abstract: Branched-chain amino acids (BCAA) are actively taken up and catabolized by the mammary gland during lactation for syntheses of glutamate, glutamine and aspartate. Available evidence shows that the onset of lactation is associated with increases in circulating levels of cortisol, prolactin and glucagon, but decreases in insulin and growth hormone. This study determined the effects of physiological concentrations of these hormones on the catabolism of leucine (a representative BCAA) in bovine mammary epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Emerging evidence shows that l-leucine has a signaling role in the small intestine to activate the mammalian target of rapamycin (mTOR), thereby stimulating protein synthesis and inhibiting proteolysis (Rhoads and Wu 2009). Similar functions of l-leucine have also been reported for other tissues, including skeletal muscle (Columbus et al 2015;Davis et al 2010;Escobar et al 2006) and mammary gland tissue (Lei et al 2011(Lei et al , 2013. Thus, either dietary supplementation with l-leucine or provision of leucine-rich meal leads to increased protein accretion in tissues (Li et al 2011a;Yin et al 2010).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Emerging evidence shows that l-leucine has a signaling role in the small intestine to activate the mammalian target of rapamycin (mTOR), thereby stimulating protein synthesis and inhibiting proteolysis (Rhoads and Wu 2009). Similar functions of l-leucine have also been reported for other tissues, including skeletal muscle (Columbus et al 2015;Davis et al 2010;Escobar et al 2006) and mammary gland tissue (Lei et al 2011(Lei et al , 2013. Thus, either dietary supplementation with l-leucine or provision of leucine-rich meal leads to increased protein accretion in tissues (Li et al 2011a;Yin et al 2010).…”
Section: Introductionmentioning
confidence: 80%
“…The intestinal development of neonates depends on the supplies of nutrients, growth factors, and hormones (Lei et al 2013;Wu et al 2013;Zabielski et al 2008). Glutamate, glutamine and aspartate are major metabolic fuels for the small intestine to maintain its digestive function and to protect the integrity of the intestinal mucosa in piglets (Wu 2009).…”
Section: Introductionmentioning
confidence: 97%
“…It is known that these amino acids are of great importance for neonatal health, growth and development. 47 …”
Section: Correlation Analysismentioning
confidence: 99%
“…This expression pattern for LAT1 is similar to the one reported previously by Aleman et al (3) in rats and Manjarin et al (20) in pigs and probably respond to the specific hormonal changes that occur during pregnancy and lactation. Recent studies have shown that Leu transamination and decarboxylation are stimulated by cortisol in rat mammary tissue and the glucocorticoid receptor NR3C1 curiously overlaps with the expression of the major milk proteins ␣-lactalbumin and ␤-casein in the porcine mammary gland (15,19). In contrast, the expression of the growth hormone receptor (growth hormone inhibits Leu transamination) tended to decreases with lactation.…”
Section: Discussionmentioning
confidence: 99%
“…The transamination reaction results in the net transfer of nitrogen from BCAA to dispensable amino acids such as Glu, and this process is hormonally regulated. Insulin and growth hormone inhibit BCAA transamination, whereas cortisol and glucagon increase it (9,15,17). This high BCAA demand suggests active BCAA transport in mammary cells.…”
mentioning
confidence: 99%